(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aimed to determine the processes of Mangngaro tradition in Messawa, Mamasa regency of West Sulawesi. The author used a qualitative ethnography method, namely conducting interviews with traditional and community leaders which is in Messawa district. The author only focuses on discussing the processes of Mangngaro culture in Messawa, Mamasa Regency, which is related to the tradition that is still strong and is still often held in the Mamasa, Messawa and surrounding area. The steps in data collection included observation method, interviewing, and documentations. The findings of this study to find out the processes of Mangngaro, that is included removed the body from Alang-alang or burrow they then carried out a parade to Lattang or rice fields that had been provided as a place of burial. At that place, the bodies were lined up overnight to carry out the process of updating the wrapper that wrapped the body. Then they carry out the process of slaughtering livestock before the body is returned to Alang-alang or Lokko and the livestock is distributed to the relatives present and adjusted to the structure or seniority in the family.